ASSESSMENT OF PLATELET ACTIVITY IN WOMEN WITH MISCARRIAGE - Kodirova Dildora Allayorovna; Ubaydullayeva Zuxra Ibragimovna; Xadjimetov Abdugafur Akhatovich (European International Journal of Multidisciplinary Research and Management Studies, 2023)
The purpose of this study is to evaluate the functional state of platelets in women with non-carrying. We examined 78 women aged 18 to 26 years, 24 of whom (Group 1) were patients with an incipient miscarriage, receiving folic acid preparations and B vitamins and (Group 2) with aborted pregnancy. Intravascular platelet activity (VAT) was determined visually using a phase-contrast microscope according to Shitikova. It has been established that when pregnancy is not carried, a consistently high activity of platelets is maintained, which is largely associated with the constancy of the level of sensitivity of their receptors to exogenous influences.